Pengaruh Motivasi Kerja Dan Ketrampilan Mengajar Terhadap Kinerja Guru SDN 44 Amban Manokwari Papua Barat: Indonesia - Sa'adah; Choeroni, Choeroni; Muchtar, Asmaji (Muallimun : Jurnal Kajian Pendidikan dan Keguruan, 2025)
This study aims to analyze the effect of work motivation and teaching skills on teacher performance at SDN 44 Amban, Manokwari, West Papua. This study uses a quantitative approach involving 20 teachers as samples. Data analysis techniques used include the T test to determine the effect of each variable partially and the F test to see the effect simultaneously. The results of the T test show that work motivation (X1) has a significance value of 0.018 and teaching skills (X2) of 0.001, both of which are smaller than the significance level of 0.05. The t-count value for work motivation is 2.612 and teaching skills is 3.823, greater than the t-table value of 2.10982. This shows that both variables have a significant positive effect on teacher performance. Meanwhile, the results of the F test show a significance value of 0.000 and an F-count of 12.508, which is greater than the F-table of 3.59, indicating that work motivation and teaching skills together have a significant effect on teacher performance. Thus, it can be concluded that both work motivation and teaching skills contribute significantly to improving teacher performance, and both support each other in creating a quality learning process